Evaluación bovinometrica del hato lechero de la facultad de ciencias agropecuarias - Universidad Técnica Luis Vargas Torres de Esmeraldas (Revista Repique, 2024)
This study was framed within the line of research of the Faculty of Agricultural Sciences entitled: production, management and sustainable development of agricultural, livestock and forestry products with an ecosystem approach. In addition, it was aligned with the sub-line of the Zootechnics career: comprehensive local, regional and national livestock development and management. The main objective was to evaluate the biometric characteristics of the dairy herd belonging to the Faculty of Agricultural Sciences. 100% of the cows that give birth were used as experimental units. The study did not use an experimental design, it only used descriptive statistics through quantitative and observational methods. The experimental variables were: Height of the haunch and withers, Width of the rump and pelvis, length of the rump, depth of the body, depth of the udder, height of the posterior insertion of the udder cm, Diameter and length of the teats. The results obtained were subjected to the following statistical tests: measures of central tendency (means) and Pearson correlation analysis. The rump width was 53.38±1.29 cm. The width of the pelvis was 20.08±0.67 cm, the height of the udder insertion in the cattle was 18±1.52 cm. The width of the rump and pelvis presented an average correlation of 0.58, where, by increasing one characteristic, the other would also improve. The morphometric characteristics evaluated in the dairy herd presented important values, where a desirable intermediate height, intermediate depth, rump width and pelvis width favorable in the production and reproduction of the cows were recorded.